Wordwall Integration in the CTL Model to Improve Students’ Interest and Cognitive Abilities in Education for Sustainable Development - atul Mawaddah, Riffa'; Khusna, Nur Isroatul (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
In this study, Wordwall-assisted technology is used within the framework of Contextual Teaching and Learning to promote sustainable education. This study aims to analyze the use of Wordwall technology in CTL to enhance students' interest and comprehension. This study employs a quantitative approach using a quasi-experimental nonequivalent control group design involving two classes. The method serves as a function. The real issue is the cement and gravel. The research participants included 36 students from each class, and data was collected using questionnaires along with pretest and posttest assessments. The data analysis involved checking for normality, checking for equal variances, and performing independent sample t-tests using IBM SPSS Statistics 27 software. The results showed that students in the experimental class had an average learning interest of 65.47, which was higher than the 61.36 in the control class, and this difference was statistically significant with a value less than 0.05. In addition, students' thinking skills improved a lot, going from 59.58 to 83.75 in the experimental class, which shows that using interactive tools like Wordwall can really boost interest and understanding, helping with education for Sustainable Development.